Примена на герила маркетинг и 2.0 технологиите за стекнување на конкурентски предности на малите бизниси (со посебен осврт на чевларските претпријатија во Куманово) - Жибак, Мила (Економски факултет, УКИМ, Скопје, 2012)
In the Republic of Macedonia, the most of the companies at the market are small and medium, which create the most important part of the country’s economy. Footwear industry is very important for the country because of the production and export of the companies, that had very big success for years, but today the situation is very different. Big, but at the same time not loyal competition, not enough materials and other inputs in the country, not enough marketing activities by companies, are just few factors that have very big impact over the footwear companies and the situation they are into. These companies see the exit of this hard situation in the specific way of work called “lon” work, which is used today more often by most of the footwear companies in Macedonia. Problems with financial capital is making the footwear companies less attractive to their customers, so they are becoming less familiar at the footwear domestic market, so it is necessary all of the companies to focus on implementation of promotional activities in their every day work. For that reason, the main interest and the object of this research is exploring the situation of the footwear industry, especially in Kumanovo, as the most famous footwear town in Macedonia and exploring the possibilities, ways and strategies for implementing guerrilla marketing and 2.0 technologies for improving the company‘s image at the eyes of the customers, employees and business partners, and improving the position at domestic market and activities in the field of advertising. Guerrilla marketing presents unconventional and unusual way of advertising the companies. On the other hand, for creating and developing a contact with external and internal environment the best way is by using 2.0 technologies by the companies. The research is based on this methodology: literature from domain and world known authors, domain and foreign Web Sites, comparative analysis, qualitative and quantitative analysis, questioner for getting better conclusions of different attitudes and opinions.
Applying guerrilla marketing and 2.0 technologies for acquiring competitive advantages for small businesses (with main focus on footwear industry in Kumanovo)
Докторска дисертација одбранета во 2012 година на Економскиот факултет во Скопје, под менторство на проф. д–р Нада Секуловска.
Keywords: footwear industry, “lon” work, guerrilla marketing, 2.0 technologies